Design and verification of HDLC data frame parallel search and decapsulation module - Qian Yong; Liu Wei (Dianzi Jishu Yingyong, 2022)
The HDLC signal link is the high level data link control(HDLC) developed by the international organization for standar- dization(ISO). The article follows the HDLC standard data link layer specification, uses the hardware description language Verilog HDL to implement a parallel structure-based HDLC frame search and decapsulation circuit, and uses System Verilog technology to build a verification platform, and randomly generates HDLC data frames to verify the correctness of the design. Using Modelsim software to simulate waveforms, during the simulation process, for HDLC data frames with a payload area of 10 bytes, the decoder circuit requires 16 clock cycles to complete the work, taking into account processing speed and flexibility. Using QuartusII software synthesis, on Altera CycloneV devices, the circuit uses 8 adaptive logic modules ALM, 24 registers, and 35 pins.